2010
DOI: 10.1111/j.1475-4754.2009.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Glass Tesserae From Mosaics in the Monasteries of Daphni and Hosios Loukas (Greece)

Abstract: In this work 51 glass mosaic tesserae from decorations of the two Greek monasteries of Daphni and Hosios Loukas were analysed by inductively coupled plasma optical emission spectroscopy, electron microprobe analysis and X‐ray powder diffraction. On the basis of the chemical analyses, after discrimination between the tesserae of the original decorations and those from other periods, it was possible to outline the distinctive traits of Byzantine mosaic tesserae. In both the monasteries, the original mosaics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…3C). Copper is the main colourant in conjunction with increased levels of iron and lead that seem to aid the precipitation of metallic copper within the glass matrices to obtain the deep red colour (Barber et al, 2009;Brill and Cahill, 1988;van der Werf et al, 2009). The red tesserae also exhibit elevated levels of chromium, nickel and arsenic relative to the other samples analysed in this study (Table 2).…”
Section: Colourants Opacifiers and Microstructurementioning
confidence: 97%
See 3 more Smart Citations
“…3C). Copper is the main colourant in conjunction with increased levels of iron and lead that seem to aid the precipitation of metallic copper within the glass matrices to obtain the deep red colour (Barber et al, 2009;Brill and Cahill, 1988;van der Werf et al, 2009). The red tesserae also exhibit elevated levels of chromium, nickel and arsenic relative to the other samples analysed in this study (Table 2).…”
Section: Colourants Opacifiers and Microstructurementioning
confidence: 97%
“…Substantial amounts of lead oxide (w2e14%) accompany these colourants in the green and red and two of the peacock coloured samples and some lead is present also in the semi-translucent blue tesserae from the Roman Baths (for the significance of lead in red glasses see e.g. Barber et al, 2009). The highest amounts of lead, however, are found in the yellow tesserae where it acts as both the colouring and opacifying agent in the form of lead antimonate (Tables 1 and 2).…”
Section: Colourants Opacifiers and Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have addressed the problem of classifying mosaic glass (Ruffini et al, 1999a(Ruffini et al, , 1999bVerità, 2000;Brill, 2002;Fiori et al, 2004;Andreescu-Treadgold et al, 2006;Vandini et al, 2006) and identified some important differences on chronological and geographical bases, starting with the use of various raw materials, colourants and opacifiers. However, a systematic and extensive study on glass mosaics has not yet been undertaken; those carried out so far (e.g., Freestone et al, 1990;Brill, 1999;Verità, 2000;Verità et al, 2002;Verità and Vallotto, 2003;Henderson, 2004;Verità and Zecchin, 2007;Boschetti et al, 2008;Arletti et al, 2008aArletti et al, , 2008bvan der Werf et al, 2009) mainly focus on a few samples coming from the same site, probably due to the value and availability of the material, often still in situ, and cover various periods of time, often not contiguous with one another. The possibilities offered by the specific case under consideration here e of working on more than 3000 loose tesserae characterised by a full range of colours e is an unique occasion for careful and precise analytical study on palaeo-Christian glass mosaics.…”
Section: Introductionmentioning
confidence: 96%